Diagnostics of cable networks of aerodrome lighting signal systems - Нерет, В. И. (Proceedings of National Aviation University (archive), 2000)
Worked and substantiated are diagnostics parameters and the algorithm of technical diagnosis of cable rings and the technique of taking decisions as to prolongation of cable rings service for a definite period depending on their real technical condition